MODEL KOLABORASI TRIPLE HELIX DALAM PENGEMBANGAN KEWIRAUSAHAAN SOSIAL UNTUK MENINGKATKAN KESEJAHTERAAN MASYARAKAT - Kwelju, Junus; Khornal, Emelin Seraf Sysilia; Batmomolin, Yosina (JURNAL BADATI, 2025)
This research examines the implementation of the triple helix model in developing social entrepreneurship to enhance social welfare. Using a systematic literature review method of 85 peer-reviewed articles published between 2017-2024, this study analyzes collaboration patterns among academia, business, and government in driving social innovation. The results demonstrate the effectiveness of the triple helix model in increasing the number of social entrepreneurs (45%), creating new employment opportunities (45%), and improving community income (35%). Critical success factors include collaborative leadership, effective coordination platforms, and long-term commitment. Digital transformation strengthens model implementation through improved coordination efficiency and impact monitoring optimization. This research provides theoretical contributions to developing multi-stakeholder collaboration models and practical recommendations for strengthening the social entrepreneurship ecosystem.